Neutronics analyses for fast spectrum nuclear systems and scenario studies for advanced nuclear fuel cycles - Grasso, Giacomo <1980> (Alma Mater Studiorum - Università di Bologna, 2010)
The present PhD thesis summarizes the three-years study about the neutronic investigation of a new concept nuclear reactor aiming at the optimization and the sustainable management of nuclear fuel in a possible European scenario. A new generation nuclear reactor for the nuclear reinassance is indeed desired by the actual industrialized world, both for the solution of the energetic question arising from the continuously growing energy demand together with the corresponding reduction of oil availability, and the environment question for a sustainable energy source free from Long Lived Radioisotopes and therefore geological repositories.